Effectiveness of play therapy based on cognitive esteem and working memory of children with hearing and speech disorders - Talebi, Kobra; Gorji, Yusef (Applied Family Therapy Journal (AFTJ), 2023)
Aim: the purpose of this research was to determine the effectiveness of play therapy based on the cognitive-behavioral approach on self-esteem and working memory of children with hearing-speech disorders. Methods: The current research is a quasi-experimental type of research. The statistical population of the research is all people (girls and boys) with hearing-speech impairment aged 8 to 12 years, who formed Tabasom rehabilitation center in Falavarjan city in 2021-22. Sampling included 30 boys and girls with hearing and speech disorders who were selected as convenience sampling and were placed in two groups of 15 people, experimental and control group. Also, analysis of variance with repeated measurements and Bonferroni's post hoc test were used to analyze the data. Results: The findings showed that the average score of active memory (inverted digits) and self-esteem after game therapy in the experimental and control groups had a significant difference (P